An extension of Aaker’s brand personality model from an Islamic perspective: a conceptual study - Ahmed, Muhammad; Jan, Muhammad Tahir (2014)
Due to high competition and low switching cost, marketers need to differentiate a brand from others that are fulfilling similar consumer needs. Brand personality is one of the effective terms that create brand differentiation. Aaker’s brand personality model that comprises of five dimensions (Sincerity, Excitement, Competence, Sophistication and Ruggedness) has opened research gates in the field of marketing. Despite considerable amount of literature reported on Aaker’s brand personality model, research scholars have also criticized it due to the limited generalizability across different countries and cultures. This conceptual paper aims to highlight criticism on Aaker’s brand personality model and proposes an Islamic brand personality model with few existing (Aaker’s dimensions) and four new dimensions. Furthermore, considering religion as an important element of culture, brand personality in Muslim collectivist countries such as Malaysia needs to be explored. Potential research on brand personality of Islamic organizations such as Islamic banks is also proposed. This will enable Islamic banks to adopt the characteristics of Islamic brand personality which will ultimately create differentiation and attract Muslim consumer market.